Role of Health Professionals in the Application of Health Information Technology - Jena, Sanjay; rnjan Mahakud, Rashmi (International Journal of Psychosocial Rehabilitation, 2025)
In the utilization of "health information technology (HIT)", the reaction of health professionals is a significant look into subject that can incompletely clarify the non-success or success of any application of HIT. The present investigation applied an adjusted version of the re-examined "technology acceptance model (TAM)" to survey the important convictions and HIT system’s acceptance in an example of health professionals (n = 135). Organized unknown polls were utilized and a crosssectional structure was utilized. The principle result measure was the expectation to utilize HIT systems. "ANOVA" was utilized to look at contrasts in TAM-related factors among doctors of medical and nurses, and no critical contrasts were found. Analysis of Various linear regression was utilized to survey the indicators of HIT utilization aims. The discoveries demonstrated that easily recognise of utilization, however not handiness, subjective norms, and significance legitimately anticipated HIT use goals. The present discoveries propose that an alteration of the first TAM approach is expected to all the more likely comprehend support of health professionals and underwriting of HIT. The easy recognition of utilization, the importance of HIT to social influences, as well as nursing professions and medical professions, ought to be tapped through information militates intending to upgrade support to the HIT in settings of healthcare.